SURGICAL PLETH INDEX AS A RELIABLE INDICATOR OF NOCICEPTION AND STRESS HORMONE RESPONSE DURING GENERAL ANESTHESIA - Dr. Seelam Bhagyavi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Surgical nociceptive stimulation can increase the risk of infection, prolong hospitalization, and raise healthcare costs. Managing surgical stress during general anesthesia is crucial to maintain hemodynamic stability. The Surgical Pleth Index (SPI), derived from normalized heart rate and pulse wave amplitude, has emerged as a potential tool to monitor nociception more accurately than traditional measures such as blood pressure and heart rate. This study evaluated the relationship between SPI and stress hormones during elective ENT surgery under general anesthesia. Methods: Eighty ASA I-II patients undergoing elective ENT procedures were randomized into two groups: SPI-guided remifentanil titration (SPI group) and traditional remifentanil dosing (control group). SPI, BIS, arterial blood pressure, heart rate, and stress hormones (ACTH, cortisol, epinephrine, norepinephrine) were monitored at baseline, intubation, maximal surgical stimulus, and post-maximal stimulus. Hormone assays were performed using reversed-phase high-performance liquid chromatography. Statistical analyses included t-tests, chi-square, Spearman’s correlation, and ROC curve analysis. Results: Baseline demographics were comparable between groups. The SPI group demonstrated significantly lower ACTH and cortisol levels during intubation, maximal stimulation, and after maximal stimulus compared to controls. Hemodynamic parameters, including heart rate and mean arterial pressure, were more stable in the SPI group. Moderate to strong correlations were observed between SPI and stress hormone concentrations, especially ACTH. SPI showed better predictive capability for stress hormone levels than heart rate, blood pressure, or BIS. Conclusion: SPI monitoring during general anesthesia provides a reliable, real-time measure of nociception and surgical stress, outperforming traditional indicators. SPI-guided analgesic administration results in improved hormonal stress response suppression and better cardiovascular stability. Incorporating SPI into anesthetic practice may enhance patient care by optimizing analgesia and reducing physiological stress during surgery.